Plasma Exosomes and Improvements in Endothelial Function by Angiotensin 2 Type 1 Receptor or Cyclooxygenase 2 Blockade following Intermittent Hypoxia - Khalyfa, Abdelnaby; Youssefnia, Nina; Foster, Glen E.; Beaudin, Andrew E.; Qiao, Zhuanghong; Pialoux, Vincent; Pun, Matiram; Hanly, Patrick J.; Kheirandish-Gozal, Leila; Poulin, Marc J.; Gozal, David (Frontiers in Neurology, 2017)
Intermittent hypoxia (IH) is associated with increased endothelial dysfunction and cardiovascular disorders. Exosomes released in biological fluids may act as vehicles for propagating such damage, modifying the functional phenotype of endothelial cells. Drug interventions, however, may provide protection for the endothelium, in spite of exosomal activity. Using an experimental human model of IH, we investigated whether the beneficial effects of two drugs, Celecoxib (CEL) and Losartan (LOS), on IH-induced vascular dysfunction was mediated via exosomes or independent of IH-induced exosomal cargo alterations. We hypothesized that the beneficial effects of Celecoxib (CEL) and Losartan (LOS) on IH-induced vascular dysfunction would be mediated via modifications of exosomal properties by the drugs, rather than by direct effects of the drugs on the endothelium. Ten male volunteers were exposed to IH (single exposure of 6 h) while receiving LOS, CEL, or placebo (P) for 4 days before IH exposures, and plasma samples were obtained from which exosomes were isolated, and incubated with naïve human endothelial cell cultures either not treated or pre-treated with LOS, CEL, or placebo (P). Functional reporter assays (monolayer impedance, monocyte adhesion, eNOS phosphorylation) revealed that the degree of exosome-induced endothelial dysfunction was similar among IH-exposed subjects independent of drug treatment. However, pre-treatment of naïve endothelial cells with LOS or CEL before addition of exosomes from IH-exposed subjects afforded significant protection. Thus, the cardiovascular protective impact of LOS and CEL appears to be mediated by their direct effects on endothelial cells, rather than via modulation of exosomal cargo.